1997
DOI: 10.1002/(sici)1096-9861(19970929)386:3<396::aid-cne5>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin 2A receptor is expressed by enteric neurons, and by interstitial cells of Cajal and enterochromaffin-like cells of the gastrointestinal tract

Abstract: Somatostatin exerts multiple effects by activating distinct G protein-coupled receptors. Here we report the cellular sites of expression of the somatostatin subtype 2A (sst2A) receptor in the rat enteric nervous system by using a C-terminus-specific, affinity-purified antiserum and immunohistochemistry. Antibody specificity was confirmed by the cell surface staining of human embryonic kidney 293 cells expressing the sst2A receptor, the lack of staining of cells expressing the somatostatin subtype 2B receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…The small decrease in somatostatin during the ascending phase did not seem to be functionally relevant, because immunoneutralization of somatostatin and application of agonists and antagonists of various somatostatin receptor subtypes had no effect on ascending contraction. The participation of SSTR2 receptors in the peristaltic reflex is consistent with immunohistochemical studies demonstrating the presence of SSTR2 receptors on enteric neurons containing VIP and NO in rat and mouse (Sternini et al, 1997;Allen et al, 2002). These findings raise the possibility of an alternative parallel pathway in which the projection of SST is directly to the inhibitory motor neuron.…”
supporting
confidence: 85%
“…The small decrease in somatostatin during the ascending phase did not seem to be functionally relevant, because immunoneutralization of somatostatin and application of agonists and antagonists of various somatostatin receptor subtypes had no effect on ascending contraction. The participation of SSTR2 receptors in the peristaltic reflex is consistent with immunohistochemical studies demonstrating the presence of SSTR2 receptors on enteric neurons containing VIP and NO in rat and mouse (Sternini et al, 1997;Allen et al, 2002). These findings raise the possibility of an alternative parallel pathway in which the projection of SST is directly to the inhibitory motor neuron.…”
supporting
confidence: 85%
“…The molecular basis for the mediation of motor neurotransmission by ICC-IM and ICC-DMP is likely to involve expression of proteins that participate in the binding and transduction of neurotransmitters. For example, previous studies have shown that ICC express a variety of receptors, including peptide receptors, such as neurokinin (19,25,32,46), somatostatin (41) and VIP receptors (7), M 2 and M 3 muscarinic receptors (7), and nucleotide receptors (5). Expression of intracellular signaling intermediates such as protein kinases (30,40) and cGMP (38,55) is also consistent with a role for ICC-IM in mediating neuroeffector functions.…”
supporting
confidence: 58%
“…The CURE no. 9452 is directed against the COOH-terminus of mouse sst2a (amino acids 331-340), and its specificity was previously established (65). Fluorescein isothiocyanate (FITC)-labeled goat anti-mouse (1:1,000, Jackson ImmunoResearch Laboratories, West Grove, PA) and tetramethylrhodamine-5-(and 6)-isothiocyanate (TRITC)-conjugated goat anti-rabbit IgG (1:1,000, Jackson ImmunoResearch Laboratories) in 0.3% Triton X-100 in PBS were added for 2 h at room temperature.…”
Section: Immunofluorescent Histochemistrymentioning
confidence: 99%